2016
DOI: 10.1177/1756283x16656735
|View full text |Cite
|
Sign up to set email alerts
|

Association of noninvasive quantitative decline in liver fat content on MRI with histologic response in nonalcoholic steatohepatitis

Abstract: Background: Magnetic resonance imaging-estimated proton-density-fat-fraction (MRI-PDFF) has been shown to be a noninvasive, accurate and reproducible imaging-based biomarker for assessing steatosis and treatment response in nonalcoholic steatohepatitis (NASH) clinical trials. However, there are no data on the magnitude of MRI-PDFF reduction corresponding to histologic response in the setting of a NASH clinical trial. The aim of this study was to quantitatively compare the magnitude of MRI-PDFF reduction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 45 publications
4
128
1
Order By: Relevance
“…Furthermore, the prognostic significance of changes in liver fat have not yet been assessed in long-term clinical trials, reduction in liver fat content by MRI-PDFF may have utility in short term trials, as previously shown. 34,45,46 Our study shows that MRI-based techniques are superior to TE for detecting any fibrosis and steatosis in NAFLD patients who may be at increased risk for mortality and other poor prognostic outcomes. Other advantages of MRI-based techniques over TE include larger area of the liver measured, which may reduce sampling variability secondary to heterogeneity of fibrosis, 9,11 and the utility of MRI-PDFF for assessing longitudinal changes in steatosis.…”
Section: In the Context Of Published Literaturementioning
confidence: 99%
“…Furthermore, the prognostic significance of changes in liver fat have not yet been assessed in long-term clinical trials, reduction in liver fat content by MRI-PDFF may have utility in short term trials, as previously shown. 34,45,46 Our study shows that MRI-based techniques are superior to TE for detecting any fibrosis and steatosis in NAFLD patients who may be at increased risk for mortality and other poor prognostic outcomes. Other advantages of MRI-based techniques over TE include larger area of the liver measured, which may reduce sampling variability secondary to heterogeneity of fibrosis, 9,11 and the utility of MRI-PDFF for assessing longitudinal changes in steatosis.…”
Section: In the Context Of Published Literaturementioning
confidence: 99%
“…Therefore, investigators have initiated seminal studies that aim to solve this puzzle by answering questions that can be answered in the near future. One such attempt was made by Patel et al ( ) using paired MRI‐PDFF and liver histology data from two high‐quality randomized trials. The investigators demonstrated that a relative reduction of 29% in liver fat on MRI‐PDFF is associated with a histologic response in NASH (defined as a 2‐point improvement in NAFLD Activity Score).…”
Section: How To Use Mri‐pdff As An Endpoint In Nash Trials?mentioning
confidence: 99%
“…The performance of PDFF as a biomarker for hepatic steatosis has also been investigated in single-center longitudinal treatment trials. In the MOZART trial (35 subjects, diagnosed NASH, treated with ezetimibe vs placebo for 24 weeks), histologic responders (reduction in NAFLD Activity Score [NAS] of two or more points) had greater relative PDFF reduction (29.3%) than non-responders (2.0%) [21]. In another randomized trial (34 subjects, diagnosed NASH, treated with N-3 fish oil vs placebo for one year), subjects treated with N3 lost more weight and showed a greater decrease in PDFF than those treated with placebo, although there were no differences in histologic response [22].…”
Section: Introductionmentioning
confidence: 99%